Switching from blue to yellow: altering the spectral properties of a high redox potential laccase by directed evolution. (February 2013) - Mate, Diana M.; Garcia-Ruiz, Eva; Camarero, Susana; Shubin, Vladimir V.; Falk, Magnus; Shleev, Sergey; Ballesteros, Antonio O.; Alcalde, Miguel
Abstract During directed evolution to functionally express the high redox potential laccase from the PM1 basidiomycete in Saccharomyces cerevisiae, the characteristic maximum absorption at the T1 copper site (Abs610T1Cu) was quenched, switching the typical blue colour of the enzyme to yellow. To determine the molecular basis of this colour change, we characterized the original wild-type laccase and its evolved mutant. Peptide printing and MALDI-TOF analysis confirmed the absence of contaminating protein traces that could mask the Abs610T1Cu, while conservation of the redox potential at the T1 site was demonstrated by spectroelectrochemical redox titrations. Both wild-type and evolved laccases were capable of oxidizing a broad range of substrates (ABTS, guaiacol, DMP, synapic acid) and they displayed similar catalytic efficiencies. The laccase mutant could only oxidize high redox potential dyes (Poly R-478, Reactive Black 5, Azure B) in the presence of exogenous mediators, indicating that the yellow enzyme behaves like a blue laccase. The main consequence of over-expressing the mutant laccase was the generation of a six-residue N-terminal acidic extension, which was associated with the failure of the STE13 protease in the Golgi compartment giving rise to alternative processing. Removal of the N-terminal tail had a negative effect on laccase stability, secretion and its kinetics, although the truncated mutant remained yellow. The results of CD spectra analysis suggested that polyproline helixes were formed during the directed evolution altering spectral properties. Moreover, introducing the A461T and S426N mutations in the T1 environment during the first cycles of laboratory evolution appeared to mediate the alterations to Abs610T1Cu by affecting its coordinating sphere. This laccase mutant is a valuable departure point for further protein engineering towards different fates.